Pengaruh Variasi Konsentrasi dan Jenis Fiksasi pada Zat Warna Alam Daun Sirsak Terhadap Ketajaman dan Ketahanan Luntur Warna pada Kain Batik - Ardhea Mayna Putri; Rois Fatoni; Agus Haerudin (Pusat riset dan Inovasi Nasional, 2023)
Indonesia is one of the countries known for its various arts and cultures. One of them is batik, batik is one part of the archipelago's culture which has many motifs and patterns that are much favored by the people of Indonesia and abroad. Soursop (Annona murocata L.) is a plant that grows and bears fruit throughout the year. Soursop leaves have many health benefits, besides that the tannin content in soursop leaves can be used as a natural dye in batik cloth which can produce a reddish brown color. In this study using the experimental method using variations in concentration (40 and 80 grams) and type of fixation (lime, alum, and arbor). With the variation method that has been used, it turns out that it has an effect on the color produced. Good research results were obtained with a concentration variation of 80 grams using alum and arbor fixation substances.